1993
DOI: 10.1111/j.2044-8260.1993.tb01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual abuse and body‐image distortion in the eating disorders

Abstract: It has been suggested that there is a link between sexual abuse and bodily self-deprecation in women with eating disorders. In order to test that model, this study considers whether reported sexual abuse is associated with body-image distortion in anorexia and bulimia nervosa. There was no association with the reported presence of a history of abuse. However, the nature of any abuse was important. In particular, women who reported more recent abuse had a substantially greater level of bodysize overestimation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(21 citation statements)
references
References 5 publications
0
20
0
1
Order By: Relevance
“…Research on the behavioral component of body image, however, is still lacking. Previous studies found no differences in the perceptive components in individuals with and without sexual abuse [11,12,13,14]. But there are discrepancies between studies regarding the cognitive-affective component.…”
Section: Introductionmentioning
confidence: 51%
“…Research on the behavioral component of body image, however, is still lacking. Previous studies found no differences in the perceptive components in individuals with and without sexual abuse [11,12,13,14]. But there are discrepancies between studies regarding the cognitive-affective component.…”
Section: Introductionmentioning
confidence: 51%
“…Gardner, Gardner, and Morrell (1990) found that sexually abused children had a response bias to report that their bodies were larger than they really were. In an eating disordered sample, Waller, Hamilton, Rose, Sumra, and Baldwin (1993) found positive correlations between BPI and age at first and most recent abuse, suggesting that women who had been abused more recently (after age 14) had a greater tendency to perceptually distort body image compared who not been abused or had been abused before the age of 14. Lastly, Bryam, Wagner, and Waller (1995) found that for women who had high levels of eating psychopathology, significant positive correlations were found between BPI ratings and both age (r = .52) and duration of abuse (r = Ϫ.52); this suggested that women who experienced abuse in pubertal years were more likely to exhibit perceptual body image distortion.…”
mentioning
confidence: 86%
“…In particular, women who reported more recent sexual abuse had a substantially greater level of bodysize overestimation (Waller, Hamilton, Rose, Sumra, & Baldwin, 1993). Exploring the impact of sexual and/or physical abuse among eating-disordered patients and asymptomatic subjects, there was no significant association between abuse experiences and the severity of the eating disorder (Favaro et al, 1998).…”
Section: Impact Of Physical and Sexual Abuse On Body Image In Edmentioning
confidence: 98%